ANALISIS IMPLEMENTASI KEBIJAKAN PRESERVASI KOLEKSI KUNO DAN LANGKA BALAI BESAR PERPUSTAKAAN DAN LITERASI PERTANIAN - Muhammad Syazarwan; Ute Lies Siti Khadijah; Yunus Winoto (Program Studi Perpustakaan dan Ilmu Informasi, Fakultas Bahasa dan Seni, Universitas Negeri Padang, 2026)
The Balai Besar Perpustakaan dan Literasi Pertanian (BB Pustaka) holds more than 11,000 antiquarian collection titles with high historical and scientific value, making preservation policy implementation a critical institutional responsibility. This study aims to analyze the implementation of preservation policies for ancient and rare collections at BB Pustaka, examine the effectiveness of operational guidelines used, and identify managerial constraints in preservation activities based on IFLA preservation principles. This research employed a qualitative method with a case study approach. Data were collected through in-depth interviews, observation, documentation, and literature study. Informants were selected using purposive sampling consisting of senior librarians, unit heads, and technical preservation staff. Data validity was tested through source triangulation and analyzed using the Miles and Huberman model. The results show that preservation policy at BB Pustaka has a normative basis derived from Ministry of Agriculture regulations, with preservation activities prioritized on Indonesiana collections. However, the existing SOP has not been optimally utilized as a work guideline due to inadequate socialization. Preservation practices largely rely on tacit knowledge transmitted informally among librarians. A digital flipbook containing detailed technical procedures was found, but it has not been formally institutionalized as an official policy document. BB Pustaka has sufficient institutional foundations and technical capacity for preservation, but requires strengthening in procedure standardization, policy documentation, and institutionalization of preservation knowledge to ensure more consistent and sustainable collection conservation.